SOVEREIGNTY AND INTERNATIONAL CRIMINAL LAW - Peruana de Derecho Internacional, Sociedad (2020)
In this article I briefly develop the issues of sovereignty from the point of view of internationallaw and how it is necessary to update the legislation of the countries, in accordance with itsprogress. Modern international law issues are essential for its application and validity and as away to effectively incorporate into the lives of citizens, therefore must be introduced into theinternal law of the countries. International law, especially the 21st century, has turn off newtwist that introduces the individual, the human person, as an element of international criminallaw, as a result of the processes that, intuitu personae, have been dealing with in theInternational Criminal Court.